Recommendations for the effective use of T-cell–redirecting therapies: a Canadian consensus statement - Lancman, Guido; Song, Kevin; White, Darrell; Crosbie, Tina; Sharif, Ismail; Emond, Marianne; Saleem Raza, Muhammad; Elias, Martine; Kaedbey, Rayan; Chu, Michael P. (Frontiers in Oncology, 2024)
BackgroundT-cell–redirecting therapies, such as bispecific antibodies and chimeric antigen receptor T-cells, exploit the cytotoxic capabilities of the immune system to destroy cells expressing specific surface antigens, including malignant cells. These therapies have demonstrated unprecedented rates, depth, and duration of responses in relapsed and refractory multiple myeloma. However, there are significant challenges in implementing these therapies into practice, which require multidisciplinary and multicenter coordination and significant healthcare resources to effectively manage these patients. So far, there are no Canadian guidelines for the effective implementation and use of T-cell–redirecting therapies.MethodsThis consensus statement was developed based on three advisory meetings held in March, July, and November 2023. During these meetings, a panel of Canadian subject matter experts and representation from Myeloma Canada gathered to discuss the optimal procedures for the use of T-cell–redirecting therapies in the treatment of multiple myeloma. Members of the panel performed a thorough review of randomized clinical trials, real-world data, and other current literature, and provided their up-to-date clinical experience with T-cell–redirecting therapies in Canadian practice settings. Subsequently, asynchronous working groups were appointed to develop unified criteria for patient selection, appraise referral pathways, and devise strategies for management of short-term and long-term adverse events arising from the use of T-cell–redirecting therapies in multiple myeloma.ResultsHere, we present recommendations for optimizing patient selection, referral pathways, and adverse event management in the Canadian practice setting. These recommendations are relevant for hematologists/oncologists, oncology nurses, pharmacists, nurse practitioners, physician assistants, and other providers who treat patients with multiple myeloma, as well as individuals with multiple myeloma and their care partners. These recommendations will be of interest to clinicians who treat patients with MM at community clinics and hospitals and who may be interested in referring patients for T-cell–redirecting therapy.